Mindfulness and marital satisfaction: direct and indirect effects - Smith, Amberly Reigh, author; Coatsworth, J. Douglas, advisor; Shomaker, Lauren, committee member; Stallones, Lorann, committee member (Colorado State University. Libraries, 2015)
This study examined the interpersonal nature of mindfulness by testing the association between mindfulness and marital satisfaction. The growing scientific study of mindfulness has emphasized how the physical body, cognitive thoughts and experienced emotions contribute to a general sense of personal wellbeing, but less focus has been on how mindfulness is connected to healthy interpersonal relationships. In a sample of 222 predominately middle-class, Caucasian, married mothers, this study tested the direct association between mindfulness and marital satisfaction and the indirect relationship operating through a general sense of wellbeing. Results indicated that a direct relationship between mindfulness and marital satisfaction was not statistically significant, but the indirect pathway of mindfulness to marital satisfaction via wellbeing emerged significant. Therefore, one possibility is that mindfulness affects marital satisfaction through creating a general sense of wellbeing for the individual. These findings encourage future research on mindfulness and marital satisfaction, and other possible pathways through which they are associated.